ESO-ESMO 3rd international consensus guidelines for breast cancer in young women (BCY3). (October 2017) - Paluch-Shimon, Shani; Pagani, Olivia; Partridge, Ann H.; Abulkhair, Omalkhair; Cardoso, Maria-João; Dent, Rebecca Alexandra; Gelmon, Karen; Gentilini, Oreste; Harbeck, Nadia; Margulies, Anita; Meirow, Dror; Pruneri, Giancarlo; et al.
Abstract: The 3rd International Consensus Conference for Breast Cancer in Young Women (BCY3) took place in November 2016, in Lugano, Switzerland organized by the European School of Oncology (ESO) and the European Society of Medical Oncologists (ESMO). Consensus recommendations for the management of breast cancer in young women were updated from BCY2 with incorporation of new evidence to inform the guidelines, and areas of research priorities were identified. This manuscript summarizes the ESO-ESMO international consensus recommendations, which are also endorsed by the European Society of Breast Specialists (EUSOMA).